Incidental acquisition of foreign language vocabulary through multi-modal situations - Bisson, Marie-Josee (2013)
There are many advantages to learning a foreign language, such as a better understanding of another culture, a better chance of employment, as well as metalinguistic and cognitive benefits. Unfortunately, language learning can be a long and difficult process, partly because of the amount of words necessary to achieve fluency in a language. However, informal exposure to languages can help language learning. The aim of this thesis was to explore the impact of informal exposure on the incidental acquisition of foreign language vocabulary with complete beginners in a foreign language. This was investigated in the context of multi-modal situations including verbal (auditory and written) and pictorial information.